Please rate after riding : the impact of formal evaluation on consumers’ feedback - Foernges, Louise Helene Gonçalves (2019)
Advances in Information Technology along with changes in society have allowed for the emergence of collaborative services. The act of sharing among peers -in substitution to ownership- is a growing phenomenon with many successful companies having arisen in the last decade. Since this new economy works mostly on the basis of sharing among strangers, mechanisms for identifying good and ‘bad’ users have become a necessity. One popular tool is a mechanism that allows for mutual evaluation among platform users (peer-providers and peer- users) using reviews and/or ratings as forms of evaluation. However, often users will give a biased feedback or attenuate negative evaluations of their peers due to the nature of collaborative services, where interactions are more personal and social norms seem to exist. This represents a problem especially in situations where the service provided has a failure that goes unreported. Although collaborative services are growing in popularity, few studies have been carried out to investigate how pro-social norms are integrated into practices and interactions between peers. To examine factors leading to feedback bias and its boundary conditions, we conducted two scenario-based experiments online using the context of an on-demand transportation service. We compared feedback (in the form of rating and tip) in a formal type of evaluation to a control condition (i.e. informal). In Study 1, we find that feedback bias in a formal evaluation system can be explained by forgiveness. Furthermore, that the type of service failure directly impacts feedback bias with perceived quality compromised by the failure being a mediator for this effect. We also find tip to be a less biased form of feedback than ratings. In Study 2, we confirm results of Study 1, and investigate overall driver score as a boundary condition for the effect of type of evaluation on feedback. Results show that a high peer score leads to feedback bias in a formal type of evaluation. Additionally, we find anticipation of guilt to be another mediator for the effect of type of evaluation on feedback. Managerial implications and suggestions for further research are discussed.